2004
DOI: 10.2190/tm7u-qrf1-0eg7-p9p7
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Verbal and Nonverbal Interaction in Conventional and Distance Learning Environments

Abstract: As increasing numbers of educational institutions implement distance learning (DL) programs, educators need to know how teaching and learning processes change when teachers and learners are no longer in the same place at the same time. Understanding the theoretical and practical implications of these changes can help teachers to compensate learners for the limitations that often characterize a DL environment. In this article, we describe how we used content analysis to identify how university lecturers' verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In addition to the impact of interaction type in reducing TD perception and increasing academic success, another factor whose impact is wondered in online learning is the instructional approach teacher will follow in the teaching process. Studies have shown that self-regulation skills play an important role in completing distance education lessons successfully, and there should be precautions to be taken to improve these (Kearsley & Lynch, 1996; Offir, Lev, Lev, Barth, & Shteinbek, 2004). According to Moore and Kearsley (2011), the students who are generally successful in online programs are the ones who manage and check their own learning process, and who have improved self-regulation skills.…”
Section: Theoretical Background Related Work and Hypothesesmentioning
confidence: 99%
“…In addition to the impact of interaction type in reducing TD perception and increasing academic success, another factor whose impact is wondered in online learning is the instructional approach teacher will follow in the teaching process. Studies have shown that self-regulation skills play an important role in completing distance education lessons successfully, and there should be precautions to be taken to improve these (Kearsley & Lynch, 1996; Offir, Lev, Lev, Barth, & Shteinbek, 2004). According to Moore and Kearsley (2011), the students who are generally successful in online programs are the ones who manage and check their own learning process, and who have improved self-regulation skills.…”
Section: Theoretical Background Related Work and Hypothesesmentioning
confidence: 99%
“…The content of that interaction also has received some focus in the literature, which finds that instructor interactions tend to be more procedural and at a lesser cognitive level with remote students. Conversely, interaction with local students is not only more social but also exists at a deeper cognitive level (Freitas, Myers, & Avtgis, 1998;Offir et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of the current distance education technologies, videoconferencing most closely approximates the face-to-face instructional experience because students and teachers can see and hear each other in real time. It is, therefore, regarded as the most interactive of these technologies (Offir, Lev, Lev, Barth, & Shteinbok, 2004). But, as McDavid (2003) points out, interaction in distance education is complicated.…”
mentioning
confidence: 99%
“…Nowadays the problems of distant (open) education are widely discussed. The following advantages of the information and distant technologies use in the educational process have been identified in the works of the researchers (Ahayan, year;Hen, 1996;Ibragimov 2005;Mioduser, Nachmias, Lahov, & Oren, 1999;Nachmias & Segev, 2003;Offir, Lev, Barth, & Shteinbok, 2004):…”
Section: Introductionmentioning
confidence: 99%